Otitis externa difusa infecciosa: revisión de la literatura - Gutiérrez C., Daniela; Fernández R., Lara; Bravo C., Gustavo; Alzérreca A., Eugenio (Revista Hospital Clínico Universidad de Chile, 2013)
External otitis (EO) is a skin infection of the external auditory canal (EAC). It’s a frequent complaint to the otolaryngologist affecting 10% of the population at least once in their life time. EO is associated with an increased humidity of the EAC, local trauma and allergic skin conditions. The diagnosis is based on clinical symptoms and signs such as earache and positive tragus sign. Infections EO are mostly bacterial infections caused by P. aeruginosa and S. aureus, and in a lower percentage fungal infection by A. niger and C. albicans. Treatment of acute infectious EO is essentially local and should be active against most common agents. The aim of this review is to update the current reality of this common clinical entity in our environment.